2023
DOI: 10.1101/2023.04.04.535539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NanoMOFs with Encapsulated Photosensitizer: Accumulation inChlamydia trachomatisInclusions and Antimicrobial Effects

Abstract: Metal-organic framework nanoparticles (nanoMOFs) are a promising class of hybrid nanomaterials for biomedical applications. Some of them, including biodegradable porous iron carboxylates are proposed for encapsulation and delivery of antibiotics. Due to the high drug loading capacity and fast internalization kinetics nanoMOFs are more beneficial for the treatment of intracellular bacterial infections compared to free antibacterial drugs, which poorly accumulate inside the cells because of the inability to cros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The use of nanoparticles as DDS for the treatment of chlamydial infections is an attractive strategy. Recently, we showed the feasibility of MIL-100(Fe) nanoMOFs to co-localize with Ctr in the infected RAW264.7 macrophages ( Figure 4 B) [ 103 ]. In the same study, a photodynamic strategy was used to eradicate Ctr using photosensitizer-loaded nanoMOFs that could find a potent application for the treatment of mucosal infections.…”
Section: Development Of Mofs For the Treatment Of Chlamydial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nanoparticles as DDS for the treatment of chlamydial infections is an attractive strategy. Recently, we showed the feasibility of MIL-100(Fe) nanoMOFs to co-localize with Ctr in the infected RAW264.7 macrophages ( Figure 4 B) [ 103 ]. In the same study, a photodynamic strategy was used to eradicate Ctr using photosensitizer-loaded nanoMOFs that could find a potent application for the treatment of mucosal infections.…”
Section: Development Of Mofs For the Treatment Of Chlamydial Infectionsmentioning
confidence: 99%
“…It has been revealed that the nanoMOF that encapsulated the photosensitizer methylene blue (MB) exhibited significant photodynamic inactivation of Ctr in infected cells resulting in a two order of magnitude bacterial burden decrease in comparison with the non-treated infected control and more than a one order of magnitude greater Ctr inhibition in comparison with free MB. Interestingly, it was found that MIL-100(Fe) nanoMOFs have an intrinsic anti-chlamydial effect presumably due to involvement into a Fenton reaction [ 103 ]. Thus, our findings suggest the use of iron(III)-based nanoMOFs as a promising drug delivery nanoplatform, which contributes to antibacterial effect, for the treatment of mucus chlamydial infections by local administration.…”
Section: Development Of Mofs For the Treatment Of Chlamydial Infectionsmentioning
confidence: 99%